Honey bee mortalities caused by direct and indirect poisoning in Hungary - Takács, Marianna; Oláh, János (Acta Agraria Debreceniensis, 2017)
Bee poisoning related top lant production shows an increasing tendency. The poisoning of honey bees most of the times is caused by neonikotinoids and insecticides. The bee pasture has imparied because of the too high bee-density,therefore the beekeepers had to locate their colonies near to the farmland. The pollinating insects experience dimmesurable damages because the ignorance of the agricultural society and the lack of communication. In cases of bee poisoning sometimes it can be intentional. The samples of direct bee-destruction show higher dose of chemical residues than the amount of which they can get during the pollinating activity. In our study we also demonstrate the direct bee poisoning which is caused by endosulfan and dichlorvos.